Design and implementation of a new multilevel inverter topology with shared power switches / Jafferi bin Jamaludin - Jafferi, Jamaludin (2014)
The increasing attention drawn on multilevel inverters particularly in medium and high power applications has led to the enhanced efforts and initiatives to improve the features and competitiveness of multilevel inverters. This research is part of such efforts and initiatives, with the intended improvement is targeted at reducing circuit complexity and cost. For this purpose, a new three-phase multilevel inverter topology based on switch-sharing approach has been proposed in this research. The topology is made up of three modules. Combination of Module 1 and Module 2 produces an arrangement of the conventional full-bridge circuit with three bidirectional switches. Module 3 comprises a string of bidirectional switches connected to DC sources. Here, the switches operate in the optimized mode. In this way, the operation of each switch is divided among the three phases. By adding one bidirectional switch in Module 3 of mlevel structure, the (m + 1)-level structure is formed. A new modulation scheme based on space vector concept with virtual vectors utilization has been developed for this topology. By using the virtual vectors, the difficulty in decomposing the reference vector in certain zones as a result of the elimination of several voltage vectors, can be effectively overcome. A proportional integral (PI) controller equipped with a new automatic tuning has been developed to deal with varying load conditions. A detailed study of the proposed four-level and five-level inverters has been described. The performance of the proposed inverter is analyzed through MATLAB/SIMULINK simulation. The hardware prototype of the proposed multilevel inverter using digital signal processors (DSPs) in implementing the proposed modulation and current control algorithms has been developed for validation.